DETERMINATIONS OF THREONINE IN MEXICAN FOODS AND IN OTHER PRODUCTS - GIRAL, JOSE; ECHEGOYEN M, BLANCA (Hospital General, CD MEXICO, DF, MEX, 1976)
Morphologic changes due to disintegration of the stroma of human erythrocytes found in skin tissue fluid from pinta lesions were observed with the electron microscope The tissue fluid was concentrated by low speed centrifugation first in saline soln, th
CIENC MEX
Keywords: DETERMINATIONS, THREONINE, MEXICAN, FOODS, PRODUCTS; CIENCIAS MEDICAS; CIENCIAS CLINICAS; PATOLOGIA CLINICA